Obtención y caracterización del biomaterial a partir del micelio de hongo (PLEUROTUS OSTREATUS) en aplicaciones de embalaje (EPS) - Ayachipo Sillagana Luis Edison (2026)
Currently, pollution is one of the most critical problems in the world, causing a significant impact on the environment and human health. Expanded polystyrene (Flex foam) is one such example, as it is non-biodegradable, pollutes water, and causes irreversible damage to marine life due to its synthetic nature. This research addresses this problem with a sustainable solution for the production of expanded polystyrene in packaging applications using a biodegradable and ecological biomaterial. The biomaterial was obtained from the mycelium of the Grey Oyster mushroom (Pleurotus ostreatus) and sawdust (wood). In this case, a Design of Experiments (DOE) Response Surfaces was implemented with the following considerations: incubation temperature, drying temperature and time, resulting in the production of 15 mixtures. The following compression tests were performed on the samples, yielding the following results for maximum stress (MPa) and maximum strain (mm) according to ASTM D3574 Test C, and hardness testing according to ASTM D2240. Finally, biodegradability tests were conducted, analyzing weight loss and the biodegradation rate in two different environments: under controlled conditions and in a natural environment over thirty days. The test results for the biomaterial show that in compression tests, the maximum stress increased by 135% compared to the conventional material (Flex Foam), while the maximum strain was 32.4% lower. Similarly, in hardness tests, the biomaterial showed an increase of 17.67%. Finally, the biodegradability tests demonstrated superior performance compared to expanded polystyrene (Flex Foam), highlighting its environmental advantages.